Diagnostic and methodological evaluation of studies on the urinary shedding of SARS-CoV-2, compared to stool and serum: A systematic review and meta-analysis - Roshandel, Mohammad Reza; Nateqi, Masoud; Lak, Ramin; Aavani, Pooya; Sari Motlagh, Reza; F. Shariat, Shahrokh; Aghaei Badr, Tannaz; Sfakianos, John; Kaplan, Steven A; Tewari, Ashutosh K (Cellular and Molecular Biology, 2020)
Investigating the infectivity of body fluid can be useful for preventative measures in the community and ensuring safety in the operating rooms and on the laboratory practices. We performed a literature search of clinical trials, cohorts, and case series using PubMed/MEDLINE, Google Scholar, and Cochrane library, and downloadable database of CDC. We excluded case reports and searched all-language articles for review and repeated until the final drafting. The search protocol was registered in the PROSPERO database. Thirty studies with urinary sampling for viral shedding were included. A total number of 1,271 patients were enrolled initially, among which 569 patients had undergone urinary testing. Nine studies observed urinary viral shedding in urine from 41 patients. The total incidence of urinary SARS-CoV-2 shedding was 8%, compared to 21.3% and 39.5 % for blood and stool, respectively. The summarized risk ratio (RR) estimates for urine positive rates compared to the pharyngeal rate was 0.08. The pertaining RR urine compared to blood and stool positive rates were 0.20 and 0.33, respectively. Our review concludes that not only the SARS-CoV-2 can be excreted in the urine in eight percent of patients but also its incidence may have associations with the severity of the systemic disease, ICU admission, and fatality rates. Moreover, the findings in our review suggest that a larger population size may reveal more positive urinary cases possibly by minimizing biases.